2014
DOI: 10.1128/aem.01196-14
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Accelerates Activation of a Novel Haloarchaeal Serine Protease That Deproteinizes Chitin-Containing Biomass

Abstract: bThe haloarchaeon Natrinema sp. strain J7-2 has the ability to degrade chitin, and its genome harbors a chitin metabolism-related gene cluster that contains a halolysin gene, sptC. The sptC gene encodes a precursor composed of a signal peptide, an N-terminal propeptide consisting of a core domain (N*) and a linker peptide, a subtilisin-like catalytic domain, a polycystic kidney disease domain (PkdD), and a chitin-binding domain (ChBD). Here we report that the autocatalytic maturation of SptC is initiated by ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…). Such a stepwise maturation process has been described for other linker peptide–containing subtilases, including Tk‐subtilisin (Tanaka et al ., ), protease CDF (Cheng et al ., ), WF146 protease (Zhu et al ., ), and SptC (Zhang et al ., ). For linker peptide‐lacking subtilases such as subtilisins E (Yabuta et al ., ) and BPN′ (Gallagher et al ., ), following autocleavage of the N‐terminal propeptide, the newly liberated N‐terminus of the mature domain moves away from the active site and contributes to the formation of a Ca 2+ ‐binding site (Yabuta et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…). Such a stepwise maturation process has been described for other linker peptide–containing subtilases, including Tk‐subtilisin (Tanaka et al ., ), protease CDF (Cheng et al ., ), WF146 protease (Zhu et al ., ), and SptC (Zhang et al ., ). For linker peptide‐lacking subtilases such as subtilisins E (Yabuta et al ., ) and BPN′ (Gallagher et al ., ), following autocleavage of the N‐terminal propeptide, the newly liberated N‐terminus of the mature domain moves away from the active site and contributes to the formation of a Ca 2+ ‐binding site (Yabuta et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Mutation analyses of the Tat signal peptides of SptA and Nep have shown that these halolysins are Tat‐dependent substrates (Shi et al ., ; Ruiz et al ., ). Nep and SptC reportedly mature autocatalytically (Ruiz et al ., ; Zhang et al ., ). These findings raise interesting questions about whether Tat‐dependent halolysins can be prematurely activated before translocation across the cytoplasmic membrane in a folded state and how haloarchaea minimize the risk of premature activation of halolysins and associated proteolytic damage to cellular proteins.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…DQ137266). The enzymatic properties, maturation, and secretion mechanisms of SptA and SptC have been characterized (25)(26)(27)(28). As the major extracellular protease of Natrinema sp.…”
mentioning
confidence: 99%